Synthesis and biological evaluation of stilbene derivatives coupled to NO donors as potential antidiabetic agents - Wang, Bing; Liu, Teng; Wu, Zhongyu; Zhang, Lei; Sun, Jie; Wang, Xiaojing (Journal of enzyme inhibition and medicinal chemistry, 2018)
The work is focused on the design of drugs that prevent and treat diabetes and its complications. A novel class of stilbene derivatives were prepared by coupling NO donors of alkyl nitrate and were fully characterised by NMR and other techniques. These compounds were tested in vitro activity, including α-glucosidase inhibitory activity, aldose reductase (AR) inhibitory activity and advanced glycation end products (AGEs) formation inhibitory activity. A class of modified compounds could play a significant effect for treatment of diabetic complications. Target compounds 3e and 7c offered a potential drug design concept for the development of therapeutic or preventive agents for diabetes and its complications.